Points, Should Be Considered by The Employers of The Hospitality Businesses for Increasing Loyalty Among Employees in Bangladesh - Islam, Md. Rafiul; Palok, Nafiul Huda (Archives of Business Research, 2023)
It’s very important to enhance the loyal behaviour of employees to get more success in the tourism and hospitality industry and compete with the competitors. The study is based on the employees of Hotel Royal International. If employees get satisfied what hospitality business owners would serve them then productivity and efficiency will reach the goal in a satisfactory manner. But if not, then the productivity and efficiency will fall apart. The objective of the study is to identify the factors of employee job satisfaction with reasons behind job dissatisfaction and to give some recommendations based on the findings that will help the hotel industry to gain the best output in productivity and efficiency. To satisfy the aim of this study data are collected from 80 employees through the questionnaire and analyzed it by using some statistical tools. In this research some factors are found that are preferred by the employees; they are satisfied with working environment, they are satisfied with Co-worker’s cooperation, they see the personal and professional growth in the organization, they are satisfied with your regular assigned activities etc. Some negative factors are identified in this research also; the employees haven’t got the training they need to do the job, they are not satisfied with the level of increment, they don’t feel flexible in Career development system, they think that their salaries don’t match to their responsibilities and they are not satisfied with the overall job security. The recommendations in that case are to give proper trainings to the employees required for the job, they re-think about their salary and increment, provide them ways to improve their flexibility in career development and overall job security.